Cassandra's Prophecies in Aeschylus' Tragedy "Agamemnon": linguopragmatic Aspect - Бєльський, Павло (Київський національний університет імені Тараса Шевченка, 2026)
Background. The image of Cassandra in Aeschylus''Agamemnon is built on the unity of opposites: prophetess and slave; unlimited knowledge and the impossibility of communicating it. This combination of incompatible qualities makes Cassandra a constant object of scholarly and artistic interest. In this article, the Cassandra scene (lines 1035–1330) is examined from a linguo-pragmatic perspective. Methods. The study employs methods of pragmalinguistic analysis: analysis of speech acts, meanings of utterances, and pauses; contextual analysis; as well as semantic and stylistic analysis of the text. Results. The article analyzes the linguo-pragmatic aspects of the Cassandra scene in Aeschylus' "Agamemnon": her eloquent silence at the beginning of the scene, the monologue accompanied by the Chorus' remarks that later develops into a full dialogue. Particular attention is paid to the speech characteristics of Cassandra's utterances, namely the large number of emotional addresses and repetitions–both interjections and full lexical items. A unique reduplication of the pronoun ἐγώ, unparalleled in the entire corpus of Ancient Greek literature, is noted separately. Numerous metaphors and images used in the prophetess' speech are examined, especially animalistic metaphors such as "wolf," "two-footed lioness," and "weak and effeminate lion." The communicative functions of the speech are then analyzed: a warning about the imminent murder; condemnation of this crime and of earlier crimes committed in the house of Agamemnon; Cassandra's self-presentation as a prophetess inspired by Apollo; attempts to establish contact with the Chorus; prayer and curse. Each of these functions is realized only partially, which creates a pragmatic conflict. The article further addresses the question of Cassandra's madness, presenting arguments in favor of interpreting it as a deliberate instrument for achieving certain aims, as well as arguments supporting the view that the heroine suffered from genuine madness in a strictly medical sense. The split of the subject is also considered: Cassandra-the-prophetess and Cassandra-the-victim are clearly distinguished in this scene and to some extent conflict with one another. The heroine's relationship with time is examined, namely her perception of past, present, and future as a single whole. Finally, the image of Cassandra in Aeschylus is compared with her mentions in Homer's "Iliad" and "Odyssey", as well as with her portrayal in Euripides' "Trojan Women", where the pragmatic aim of her speech is significantly shifted. Conclusions. The analysis demonstrates that the image of Cassandra in Aeschylus' Agamemnon is constructed on contrasts and contradictions, which is underscored by the presence of numerous questions that remain open to scholarly debate.

Вступ. Образ Кассандри в трагедії Есхіла "Агамемнон" побудований на єдності протилежностей: провидиця й рабиня; необмежене знання й неможливість повідомити його. Таке поєднання несумісних якостей робить образ Кассандри предметом постійного наукового й художнього інтересу. У цій статті сцену Кассандри (рядки 1035–1330) розглянуто в лінгвопрагматичному аспекті. Методи. У дослідженні використано методи прагмалінгвістичного аналізу: аналіз мовленнєвих актів, значень висловлювань і пауз; контекстуальний аналіз; семантичний і стилістичний аналіз тексту. Результати. У статті розглядається лінгвопрагматичний аспект сцени Кассандри в трагедії Есхіла "Агамемноні": її промовисте мовчання на початку сцени, монолог у супроводі реплік хору, який потім переходить у повноцінний діалог. Мовленнєві особливості промови Кассандри: значна кількість емоційних звертань і повторів – як вигуків, так і повнозначних слів. Окремо зауважено унікальну для всього корпусу редуплікацію займенника ἐγώ. Аналізуються численні метафори й образи, використані в словах провидиці, зокрема анімалістичні метафори: "вовк", "двонога левиця", "млявий і розніжений лев". Далі розглядаються комунікативні функції промови: попередження про вбивство, яке ось-ось має відбутися; осуд цього злочину й злочинів, що відбувалися в домі Агамемнона раніше; самопрезентація Кассандри як провидиці, натхненної Аполлоном; спроби встановити контакт із хором; молитва і прокляття. Кожна із цих функцій реалізується лише частково, що і створює прагматичний конфлікт. Досліджується питання безумства Кассандри, наводяться аргументи на користь того, що це безумство було лише інструментом досягнення певних цілей, і аргументи на користь того, що героїня страждала від фактичного безумства. Розглядається також роздвоєння суб'єкта: Кассандра-пророчиця і Кассандра-жертва чітко розмежовуються в цій сцені та певним чином конфліктують одна з одною. Розглянуто відносини героїні з часом, сприйняття нею минулого, теперішнього й майбутнього часу як одного цілого. Також здійснюються порівняння образу Кассандри в Есхіла з її згадками в поемах Гомера "Іліада" та "Одіссея", а також із образом Кассандри в трагедії Евріпіда "Троянки", де значною мірою зміщується прагматична мета промови. Висновки. Аналіз показує, що образ Кассандри в трагедії Есхіла "Агамемнон" побудований на контрастах і протиріччях, що підкреслено наявністю багатьох питань, які залишаються дискусійними.
Пророцтва Кассандри в трагедії Есхіла "Агамемнон": лінгвопрагматичний аспект
Keywords: Cassandra; Agamemnon; Aeschylus; linguo-pragmatics; repetition; communicative functions; self-presentation; split subject; Кассандра; Агамемнон; Есхіл; лінгвопрагматика; повтори; комунікативні функції; самопрезентація; роздвоєння суб'єкта